Awjuh Al-Ikhtilaf Baina As-Siratain Adz-Dzatitain (Al-Ayyam li Taha Hussein wa Ake li Wole Soyinka) - Zubair, Abdulhakeem (el Harakah: Jurnal Budaya Islam, 2020)
الدراسة المقارنة هي فن من فنون الأدب التي تعزز تلاقي الأفكار والمعرفة والثقافة. ولقد تلقى هذا النوع من الدراسة عناية فائقة لدى الدارسين في اللغة العربية والإنجليزية في العصر الحديث. ومع ذلك، كانت مقارنة العمل الأدبي العربي بالعمل الأدبي الإنجليزي نادرًا جدًا في مجال الدراسات العربية في نيجيريا. لذلك ركّزتُ هذه الورقة على استنباط ودراسة أوجه الاختلاف بين كتابي «الأيام» لطه حسين و«أكى سنوات الطفولة»لـ Wole Soyinka (وولي شوينكا). ومن أهدافها أن تقوم بمقارنة وتباين مضامين العملين الأدبيْين، وتحليل الجانب الفني والسردي في الكتابين المقارنين وتوضيح بعض سلوك الطفولة على الرغم من خلفية منطقتيهما وأيديولوجيتيهما ودينيهما المختلفين؛ واعتمدت الدراسة على منهجين أساسي ينهما المنهج التاريخي والمنهج التحليلي؛ أما المنهج التاريخي فيتناول نبذة يسيرة عن حياة كل من الأديبين من خلال الدراسة. والمنهج التحليلي عبارة عن دراسة السيرتين الذاتيتين للأديبين، وتمّ تحليلهما على المعايير الأدبية والفنية. وفي الختام أثبت هذا البحث أنّ السيرتين تعكسان حياة الطفولة للکاتبين مع الاختلاف في البيئة والثقافة، وكلا العملين يتفق مع المعايير الفنية والقواعد اللغوية الموضوعة في كلتي اللغتين مع اختلافهما في أسلوب الكتابة. وأوصت الدراسة أنتترجم أعمال وولي شوينكا إلى اللغة العربية وأعمال طه حسين إلى الإنجليزية كما تحثّ الباحثين أن يركّزوا عنايتهم على تجارب الطفولة في أعمال الأدباء الأفارقة رغم اختلاف بيئاتهم وثقافاتهم؛ لاستنباط الفوائد والمعلومات من تلاقي الأفكار والمعارف. Comparative study is an art of literature promoting the convergence of ideas, knowledge and culture. This type of study has received great concern among students of Arabic and English in the modern era. However, the comparison between Arabic and English literary work is very rare in the field of Arabic studies in Nigeria. Therefore, this paper focuses on the differences between the books, “Al-Ayyam” by Taha Hussein and “Ake Years of Childhood” by Wole Soyinka. Its objectives were to compare and contrast the contents of the two literary works, to analyze the artistic and narrative side of them, and to clarify some childhood behaviours despite their different backgrounds in their regions, ideologies and religions. This study relied on two basic approaches, the historical and analytical methods. The historical method deals with a simple overview of the lives of both writers. The analytical method includes studying the writers’ biographies analyzed based on literary and artistic criteria. In conclusion, the findings show that the two biographies reflect the writers’ childhood with the difference in the environment and culture. Besides, both works are consistent with the technical standards and the linguistic rules established in both languages with their differences in writing style. The study recommended that Soyinka’s work is translated into Arabic and Hussein’s work into English. Researchers should focus more on the works of African writers despite their different environment and cultures to derive benefits and information from the convergence of ideas and knowledge.